Study of texture and recrystallization in commercial pure copper wire with and without heat treatment - Baci, Lamine; Boumerzoug, Zakaria; Esnouf, Claude (Journal of Applied Engineering Science & Technology, 2018)
Wire drawing is a necessary operation for the production of small diameter electrical wires. During this process, the shaping of the material is performed by a plastic deformation mechanism. The change in the shape of the metal causes the plastic deformation of each grain of the crystalline metal. In this work, we have studied a commercial copper wire. In this study, optical microscopy, electron microscopy transmission, Vickers hardness and X-ray diffraction were used. It is found that cold drawn wires are characterized by texture formation and dislocation cell rearrangement. Isothermal treatments were applied on the deformed yarns, which makes it possible to observe a recrystallization reaction which restores the mechanical properties and the initial structure.